Antimicrobial Activity of the Synthesized of Copper Chalcogenide Nanoparticles - N. G. Mbewana-Ntshanka; M. J. Moloto; P. K. Mubiayi (Journal of Nanotechnology)
Antimicrobial activity of copper chalcogenides nanoparticles was investigated by synthesizing copper selenide, copper sulfide, and copper oxide via the hot-injection method. Since reaction time has a profound effect on the nanocrystals size and shapes, the effect of reaction time was also investigated during the synthesis of the copper chalcogenides to obtain nanocrystals with desired properties. The reaction time showed no effect on the phase composition of the synthesized copper sulfide, copper oxide, and copper selenide nanoparticles. However, the size variation of nanoparticles with different reaction time was observed. Reaction time of 30 minutes gave the best optical (the shape of the absorption band edge and emission maxima values) and structural (size distribution of particles) properties for CuSe and CuS compared to other reaction times (15, 45, and 60 min). Their band edges were located at 506 (2.45 eV) and 538 nm (2.30 eV), respectively. For this reaction time, copper selenide produced nanoparticles with a size range of 1–27 nm and copper sulfide nanoparticles ranged 1–18 nm. The morphologies of both chalcogenides at 30 min reaction time were spherical. Reaction time of 15 minutes gave the best optical and structural properties for copper oxide nanoparticles with a band edge of 454 nm (2.73 eV) and particle size ranging 0.8–3.2 nm, but nonetheless, 30 min was used as the optimum reaction time for all three chalcogenides. The optimum parameter (220°C, 30 min, and 1 : 1 ratio) was used to synthesize the three copper chalcogenides which were then tested against Gram-negative (E. coli and P. aeruginosa), Gram-positive (S. aureus and E. faecalis), and fungi (C. albicans) employing both agar disk diffusion and minimum inhibitory concentration (MICs) methods. Copper oxide nanoparticles showed more sensitivity towards four bacterial microorganisms than the other two chalcogenides followed by copper sulfide nanoparticles with copper selenide nanoparticles being the least sensitive. The sensitivity of copper oxide nanoparticles is attributed to the smaller size of oxygen atom which strongly affects its reactivity and stability and hence very stable and highly reactive compared to sulfur and selenium.